Count me in: Understanding political consumerism and political participation and their antecedents - Gülen, Ertem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2018)
Political consumerism is a form of self-expression where consumers boycott or buycott a brand, company or a product. The increase in the amount of these actions in recent years has led scholars and marketers improve their understanding of how and why consumers engage in political consumerism and what its predecessors are. By employing a wide scale survey among 360 participants in Turkey, this study presents empirical and qualitative evidence for boycott behavior. The results revealed that women are more likely to engage in political participation and income level, political interest level and online political participation have positive effect on political consumerism, while conservatism and communicational digital media use have negative effects. The findings of the thesis are vital, as it also showed there is no significant impact of education and age on political consumerism contrary to literature.
Keywords: Consumption (Economics) -- Political aspects.; Political participation.; Consumers -- Political activity -- Turkey.